2002
DOI: 10.1007/s00439-002-0820-5
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive renal glucosuria attributable to a mutation in the sodium glucose cotransporter (SGLT2)

Abstract: Patients with primary renal glucosuria have normal blood glucose levels, normal oral glucose tolerance test results, and isolated persistant glucosuria. Congenital renal glucosuria is postulated to be attributable to defects in the SGLT2 gene. The Na(+)/glucose cotransporter gene SGLT2 (= SLC5A2) was analyzed in a Turkish patient with congenital isolated renal glucosuria. Genomic DNA was used as a template for amplification by the polymerase chain reaction of each of the 14 exons of the SGLT2 gene. The amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…However, these individuals have little or no glucosuria. In contrast, those who have SGLT2 gene mutations have persistent renal glucosuria, with glucose excretion of up to 160 g/day in severe cases (180, 381, 543, 563, 667). Recently we directly localized the expression of SGLT2 protein to the apical brush border of the early proximal tubule and demonstrated by free-flow micropuncture that SGLT2 KO mice lack glucose reabsorption in the early proximal tubule and that fractional renal reabsorption of glucose is reduced compared with wild-type mice (36 ± 8 vs. 99.7 ± 0.1%) and varied inversely with the amount of filtered glucose in the KO mice (between 60% and 10%) (656).…”
Section: Tubular Function In Diabetesmentioning
confidence: 99%
“…However, these individuals have little or no glucosuria. In contrast, those who have SGLT2 gene mutations have persistent renal glucosuria, with glucose excretion of up to 160 g/day in severe cases (180, 381, 543, 563, 667). Recently we directly localized the expression of SGLT2 protein to the apical brush border of the early proximal tubule and demonstrated by free-flow micropuncture that SGLT2 KO mice lack glucose reabsorption in the early proximal tubule and that fractional renal reabsorption of glucose is reduced compared with wild-type mice (36 ± 8 vs. 99.7 ± 0.1%) and varied inversely with the amount of filtered glucose in the KO mice (between 60% and 10%) (656).…”
Section: Tubular Function In Diabetesmentioning
confidence: 99%
“…A total of 44 different mutations have been described for the SCL5A2 gene, including missense and nonsense mutations, small deletions (in-frame and frame shift), and splicing mutations, scattered throughout the gene [8]. Although no other complications are known to be consistently associated with mutations of this gene, it is a rare genetic disorder and not well studied [912]. New free-flow micropuncture studies in mice lacking SGLT2 confirmed a lack of glucose reabsorption in the early proximal tubule and showed that fractional renal reabsorption of glucose is reduced compared with wild-type mice (36 ± 8 vs. 99.7 ± 0.1%) and varied inversely with the amount of filtered glucose in the knockout mice (between 60 and 10%) [13].…”
Section: Sglt2 and Glucose Reabsorption In The Proximal Renal Tubulementioning
confidence: 99%
“…Fumarate hydratase (FH) deficiency leads to defects in glutamate oxidation in kidney and other tissues [43], [44], which is also consistent with the decreased indirect renal reabsorption of glutamate predicted by the model. Renal glucosuria, recapitulated in the model, results from deficiency in a sodium-glucose transporter (SLC5A2) [45]. Dicarboxylicamino aciduria [46] exhibits impaired renal glutamate and aspartate reabsorption and hypoglycemia resulting from a deficient glutamate transporter (SLC1A1), all symptoms predicted by the model.…”
Section: Resultsmentioning
confidence: 90%